Haptic floor for virtual balance training - Cikajlo, I.; Oblak, J.; Matjacic, Z. (2011 IEEE World Haptics Conference, 2011)
Replacing the traditional balance training task with tasks in virtual environment in subjects after stroke was a step toward independent rehabilitation. The virtual reality supported balance training relieved the physiotherapist from strenuous work, besides, also enabled rehabilitation treatment on individuals home and functional balance ability assessment. However, adding a haptic floor to the virtual reality balance training enhanced the approach to the postural response training and assessment. We have developed a two degrees of freedom, position controlled, haptic floor plates providing postural perturbations according to the collisions with obstacles in the virtual environment. The subject generated a postural response to stabilize the body during balance training. Such task represents for the subject with stroke a serious challenge. However, the standing frame prevented the possibility to fall. The virtual reality supported balance training with haptic floor was so far carried out in healthy individuals and tested in single subject after stroke. A basic response characteristic of haptic floor was examined. The preliminary results demonstrated a sufficient dynamics of the haptic floor and great acceptability among the participating subjects. Thus the additional haptic feedback in goal based balance training may contribute to the improvement of subject's functional balance and postural abilities and so increase the quality of life. However, to confirm the clinical applicability of the haptic floor in balance training and evaluation of postural responses, a further study including clinical tests within a larger group of stroke population should be carried out.